Iron gray sea [compact disc, unabridged] : destroyermen - Anderson, Taylor, 1963- (Anderson, Taylor, 1963- Destroyermen, 2012)
In Anderson's Destroyermen series, a parallel universe adds an extraordinary layer to the drama of World War II. With every hard-won victory and painful defeat, Matt Reddy and the Allies encounter more friends - and even more diabolical enemies.